Dual‐band multifunctional metasurface for absorption and polarization conversion. Issue 7 (25th February 2020) - Dutta, Rahul; Mitra, Debasis; Ghosh, Jeet
Abstract: In this paper, a multifunctional metasurface capable of switching between an absorber and a polarization converter is presented. The active metasurface comprises diamond‐shaped unit cells embedded with PIN diodes. The characteristic of the design lies in its capability of exhibiting multifunctionality at the same frequency of operation. The structure behaves as an absorber and linear polarization converter around 15 and 17 GHz when the PIN diode is switched ON and OFF, respectively. The working principle is demonstrated with the help of simulated results. Finally, the design is fabricated and measured, and it is seen that the results are in accordance with that of the simulated ones, establishing the concept behind switchability of absorber and polarization converter.